Viabilidad financiera para la constitución y comercialización de huevos en el municipio de Ortega Tolima y municipios aledaños - Novoa Silva, Ricardo Andres; Caviedes Coral, Yeimi Paola (Universidad Antonio Nariño, 2023)
The purpose of this project is to evaluate the financial viability for the constitution and commercialization of eggs in the municipality of ortega Tolima and surrounding municipalities, where its main objective is the production of semi-creole eggs 1 for sale where with the help of the feed provided to the hens based on concentrate and natural corn which guarantees the quality of the egg, thus being much more nutritious and healthy for the consumer since at present they are looking above all for more natural at the time of feeding, for this purpose the viability of a shed of New Hampshire breed laying hens